PERANCANGAN SISTEM INFORMASI PENYEWAAN RUSUN OTORITA BATAM BERBASIS WEB - ZAHARA, MUTHIA; Harman, Rika (LPPM Universitas Putera Batam, 2021)
As the party that manages the Batam city flats, it is hoped that Disperkim will be able to provide good service and deliver information that is easy for residents to understand. One of the obstacles that exist in the Batam Authority Flats is the lack of information about the Batam Authority Flats rental process, it is also difficult for admins in managing the data that is collected. still a paper archive. So we need a system that functions to facilitate the rental process at the Batam Authority flats that uses the PHP programming language and the method used is the waterfall method and MySQL as the database. Where the purpose of this research is as follows to facilitate and assist the Admin in terms of data management of the Web-based Batam Authority Flats rental information system, as well as make it easier in terms of making reports on the Batam Authority Flats tenant information system, also facilitating the provision of information to parties parties who need the data on the rental of the Batam Authority Flats based on the Web, and using the new web-based information system as a substitute for the old system.